Work/household, transport, and leisure domains account for the sex gap in physical activity in Chile - Suárez-Reyes, Mónica; Fernández-Verdejo, Rodrigo (Frontiers in Public Health, 2022)
Background: Women usually have lower levels of moderate-vigorous physical activity (MVPA) than men. This sex gap can be accounted for by differences in MVPA in the work/household, transport, and/or leisure domains. Identifying where the differences lay in a context-specific manner may help close the gap. We aimed to compare MVPA by domain, and the relative contribution of each domain to total MVPA, between men and women in Chile. Methods: We analyzed the cross-sectional National Health Survey of Chile 2016-2017 (n=5,056, 64% women, ≥18 years-old). MVPA was estimated with the Global Physical Activity Questionnaire. MVPA was expressed in METxmin/week, and the relative contribution to total MVPA by each domain was expressed as percentage. Analyses were conducted including all participants, and also including participants reporting >0 METxmin/week of MVPA (relative contributions can only be computed in the latter). Results: Including all participants, women (vs. men) had lower MVPA (median [25th percentile –75th percentile]) for work/household (0 [0–960] vs. 0 [0–5,760] METxmin/week), for transport (360 [0–1,200] vs. 600 [0–1,680] METxmin/week), and for leisure domains (0 [0–0] vs. 0 [0–480] METxmin/week). Including only participants with >0 METxmin/week of MVPA, women (vs. men) had lower mean relative contributions to total MVPA from work/household (31.3% vs. 35.9%) and leisure domains (10.8% vs. 16.3%, respectively), but higher from the transport domain (57.9% vs. 47.8%). Conclusion: In Chile, differences in all physical activity domains account for the sex gap in MVPA. Strategies to break job stereotypes, increase opportunities for leisure, and ease active transport are required to encourage MVPA in women.